Strain improvement of Pleurotus giganteus (BERK.) Karunarathna & K. D. Hyde Via conventional mating techniques / Ha Kwan Yun - Ha , Kwan Yun (2020)
Recently, a commercial strain of Pleurotus giganteus (Berk.) Karunarathna & K.D. Hyde from China has been cultivated in Malaysia. Pleurotus giganteus was prone to insect infestation which led to heavy losses for farmers. The aim of this study was to generate new hybrids of P. giganteus that maybe resistant to pest and contamination. The commercial strain of P. giganteus from China (KLU-M 1227) and a wild strain from Malaysia (KLU-M 1391) were subjected to intraspecific breeding. Of the 56 combinations, 16 hybrids were obtained. All the 16 hybrids together with the parents were subjected to radial and linear growth study. Based on the median value, the hybrids were grouped into slow-growing with radial growth rate < 0.715 cm/day and linear growth rate < 0.295 cm/day, and fast-growing with radial growth rate ≥0.715 cm/day and linear growth rate ≥ 0.295 cm/day. The fast-growing strains with higher linear growth rate were tested for susceptibility to Trichoderma saturnisporum. The parents and three hybrids which were least susceptible to T. saturnisporum were cultivated. The parents and hybrids showed variation in the number of days for primordia formation and number of fruit bodies formed. Hybrid IH 32 gave the highest yield. The average biological efficiency of hybrid IH 32 for all the three generations was 479.66% higher compared to the parent KLU-M 1227 and 32.35% higher compared to the parent KLU-M 1391. The hybrid IH 32 had high nutritive values as it contained per 100g (dry weight): protein (16.3g), very high carbohydrate (6.8g), dietary fiber (2.73g), essential fatty acid, minerals, essential amino acids and vitamin B1 (7.8mg) and vitamin B3 (73.1mg).